The Grecian anomalous blue Polyommatus (Agrodiaetus) aroaniensis (Brown, 1976) (Lepidoptera: Lycaneidae) discovered in Croatia, at the north-western edge of its distribution - Toni Koren; Boris Lauš (Natura Sloveniae)
In 2014 and 2015, a survey to improve the knowledge about the distribution of butterflies of the subgenus Polyommatus (Agrodiaetus) was carried out in southern Croatia. The first observations of a new species for the country, P. aroaniensis, were made. These localities present the northwesternmost points of the species distribution, with the closest known population occurring in Bosnia and Herzegovina. New localities for the three species, P. admetus, P. damon, and P. ripartii, were also recorded, extending the range of the latter two species. Our findings increase the number of recorded butterfly species in Croatia to 197.